2022
DOI: 10.1101/2022.12.08.519637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell profiling identifies clinically relevant interactions between tumor associated macrophages and blood endothelial cells in diffuse large B cell lymphoma

Abstract: Diffuse large B cell lymphoma (DLBCL) and follicular lymphoma (FL) are the two most common B-cell lymphomas and are characterized by a dynamic crosstalk between tumor B cells and a heterogeneous tumor-supportive microenvironment, including immune, endothelial, and stromal components. Although their impact on the pathogenesis and prognosis of B-cell lymphoma has been acknowledged for years, tumor-associated macrophages (TAM) have not been extensively explored in DLBCL and FL. Herein, we investigate mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…Assessment of the healthy B cell pool of patients to find disease mechanisms [128] DLBCL Evaluation of the intertumoral and intratumoral heterogeneity [129] Identification of clinically relevant interactions between tumor-associated macrophages and blood endothelial cells [130] Finding proteins overexpressed in relapsed and refractory patients [131] Comparison of major immune subsets in DLBCL and double-hit lymphoma [132] Identification of differences in immune cell compartments across various stages of MM and healthy individuals [133] Description of the immune tumor microenvironment in patients with MGUS and MM at diagnosis and post-initial therapies [134] Analysis of the immune checkpoint signature and regulation [135] Characterization of NK cells in newly diagnosed cases [136] Understanding of the molecular and cellular complexities underlying disease heterogeneity and prognosis [137] Provision of insights into the mechanism of action of daratumumab and the anti-PD-L1 monoclonal antibody atezolizumab [138] MM Employment of protein profiling as a tool for prognosis and treatment stratification [139] Other Tools RRPA CLL Prediction of survival outcomes based on the proteomic signature [140] Protein Microarrays FL Identification of antibodies that distinguish lymphoid follicles in FL and benign follicular hyperplasia [141] MCL Monitoring of patient serum proteomes to identify treatment-modulated proteins linked to the presence of minimal residual disease [142] Western Blot MCL Definition of the pathologic hallmark of MCL as a tool for the diagnosis [143] araCTP, Next, we describe the basis of the main protein-based strategies employed for studying B cell malignancies.…”
Section: Analysis Of the Tumor Microenvironment To Find Differences I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the healthy B cell pool of patients to find disease mechanisms [128] DLBCL Evaluation of the intertumoral and intratumoral heterogeneity [129] Identification of clinically relevant interactions between tumor-associated macrophages and blood endothelial cells [130] Finding proteins overexpressed in relapsed and refractory patients [131] Comparison of major immune subsets in DLBCL and double-hit lymphoma [132] Identification of differences in immune cell compartments across various stages of MM and healthy individuals [133] Description of the immune tumor microenvironment in patients with MGUS and MM at diagnosis and post-initial therapies [134] Analysis of the immune checkpoint signature and regulation [135] Characterization of NK cells in newly diagnosed cases [136] Understanding of the molecular and cellular complexities underlying disease heterogeneity and prognosis [137] Provision of insights into the mechanism of action of daratumumab and the anti-PD-L1 monoclonal antibody atezolizumab [138] MM Employment of protein profiling as a tool for prognosis and treatment stratification [139] Other Tools RRPA CLL Prediction of survival outcomes based on the proteomic signature [140] Protein Microarrays FL Identification of antibodies that distinguish lymphoid follicles in FL and benign follicular hyperplasia [141] MCL Monitoring of patient serum proteomes to identify treatment-modulated proteins linked to the presence of minimal residual disease [142] Western Blot MCL Definition of the pathologic hallmark of MCL as a tool for the diagnosis [143] araCTP, Next, we describe the basis of the main protein-based strategies employed for studying B cell malignancies.…”
Section: Analysis Of the Tumor Microenvironment To Find Differences I...mentioning
confidence: 99%
“…Other myeloid cells not extensively investigated in DLBCL disease are the tumor-associated macrophages (TAM). Using mass cytometry, Ferrant et al [130] reported a co-regulation between TAMs and the activation status of blood endothelial cells in lymphoma via an alteration of the annexin A1 and the formyl-peptide receptor axis.…”
Section: Proteomics Studies On Diffuse Large B Cell Lymphoma (Dlbcl)mentioning
confidence: 99%